2021
DOI: 10.1126/sciimmunol.abe1935
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous innate immune tolerance is mediated by epigenetic control of MAP2K3 by HDAC8/9

Abstract: The skin typically tolerates exposure to various microbes and chemicals in the environment. Here, we investigated how the epidermis maintains this innate immune tolerance to stimuli that are recognized by Toll-like receptors (TLRs). Loss of tolerance to TLR ligands occurred after silencing of the histone deacetylases (HDACs) HDAC8 and HDAC9 in keratinocytes. Transcriptional analysis identified MAP2K3 as suppressed by HDAC8/9 activity and a potential key intermediary for establishing this tolerance. HDAC8/9 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

7
2

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Our results here demonstrate that CDK12 and SPT6 act in the same pathway to promote epidermal differentiation whereas other elongation factors are necessary for other aspects of skin physiology. For example, we previously showed that the FACT complex (SSRP1 and SPT16) is not essential for epidermal differentiation but is necessary for transcription elongation of MAP2K3 to mediate the skin inflammatory response 37,56 . In addition, ELL which is part of the super elongation complex has no impact on differentiation of the skin but is essential for proliferation of epidermal stem and progenitor cells 8,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results here demonstrate that CDK12 and SPT6 act in the same pathway to promote epidermal differentiation whereas other elongation factors are necessary for other aspects of skin physiology. For example, we previously showed that the FACT complex (SSRP1 and SPT16) is not essential for epidermal differentiation but is necessary for transcription elongation of MAP2K3 to mediate the skin inflammatory response 37,56 . In addition, ELL which is part of the super elongation complex has no impact on differentiation of the skin but is essential for proliferation of epidermal stem and progenitor cells 8,57 .…”
Section: Discussionmentioning
confidence: 99%
“…STING is a crucial positive immune driver that induces the production of type I IFN by triggering intracellular pathogens, such as viruses [ 14 ]. STING-mediated type I IFN promotes the activation of acquired immune responses mediated by antigen-presenting cells and enhances downstream cytotoxic immune reactions [ 9 ].…”
Section: The Mechanism Of Sting Signalingmentioning
confidence: 99%
“…Type I interferon (IFN) is a representative inflammatory cytokine that activates the acquired immune response mediated by antigen-presenting cells and subsequently drives cytotoxic cell expansion and activation [ 8 , 9 ]. Type I IFN is currently used to treat malignancies [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the action of miRNA is considered to be: (1) specific changes in the methylation pattern, (2) post-transcriptional modifications of specific histone proteins, (3) differences in chromatic packing, in addition to (4) the role of the Polycomb and Thritorax proteins, which can be used as markers. Epigenetic changes can modulate gene transcription not to alter DNA sequencing information by histone modification and DNA methylation [ 35 ]. miRNA also plays a pivotal role in the regulation of epigenetics [ 36 , 37 ].…”
Section: Clinical Sign and Biomarker For Drug Eruptionmentioning
confidence: 99%